Analysis for Science Librarians of the 2016 Nobel Prize in Physics: New Phases of Matter. Issue 1 (2nd January 2017) - Bohémier, Kayleigh Ayn
ABSTRACT: The Royal Swedish Academy of Science has awarded the Nobel Prize in Physics for 2016 to three esteemed condensed matter physicists, David James Thouless (Emeritus, University of Washington), John Michael Kosterlitz (Brown University), and F. Duncan M. Haldane (Princeton University), for their critical theoretical work in topological phase transitions and its implications for studying strange phases of matter. This article provides an analysis of the citation and coauthorship patterns of each of the Nobel Prize winners after a brief introduction to the science that won the prize.